Profile on ECG Changes in different types of Stroke in Patients at Tertiary Level Hospital in Eastern Nepal - Thakur, Manoj Kumar; Chhetri, Gaurav; Shrestha, Risab (Journal of Nobel Medical College, 2018)
Background : Physician knew for centuries that primary cardiac disorders leads to stroke, but it is recent realization that strokes may produce cardiac abnormalities. It is essential to distinguish whether cardiopulmonary abnormalities are caused by the stroke or unrelated. It is very difficult to distinguish because pre-existing cardiac abnormalities are highly prevalent in stroke. This study is designed to see ECG changes in stroke that can help for further evaluation and management.Methods and Materials: This descriptive Cross-Sectional hospital-based study was conducted to describe the ECG changes, character of ECG abnormalities in patients with stroke. All the patients admitted in the Nobel Medical College in one-year meeting inclusion criteria and residing in Eastern part of Nepal were included. Both Ischaemic and Haemorrhagic stroke were taken. ECG changes includes QTc-prolonged, AF (Atrial Fibrillation), T inversion, QRS prolonged, PR prolonged, ST elevation, ST depression, Hyperacute T wave in different types of stroke was evaluated on the basis of age, sex, smoker, HTN and DM.Result : The total participants were 100. Out of which 65 were male and 35 were female and 72.0% were 60 years and above and 28.0% below 60 years with Mean Age in year ± Standard deviation of male and female was (64.74 ± 12.62) and (63.69 ± 13.53) respectively. Ischemic and Haemorrhagic stroke was 87.0% and 13.0% respectively. ECG changes were found in 84.0%.Conclusion:  Ischaemic stroke (87.0%) was more common than Haemorrhagic stroke (13.0%). ECG changes were in 84.0% and QTc-prolonged (29.0%) was the most common followed by AF (27.0%).Journal of Nobel Medical CollegeVolume 6, Number 2, Issue 11 (July-December, 2017) Page: 42-47